The Molecular Functions of MeCP2 in Rett Syndrome Pathology - Sharifi, Osman; Yasui, Dag H. (Frontiers in Genetics, 2021)
MeCP2 protein, encoded by the MECP2 gene, binds to DNA and affects transcription. Outside of this activity the true range of MeCP2 function is still not entirely clear. As MECP2 gene mutations cause the neurodevelopmental disorder Rett syndrome in 1 in 10,000 female births, much of what is known about the biologic function of MeCP2 comes from studying human cell culture models and rodent models with Mecp2 gene mutations. In this review, the full scope of MeCP2 research available in the NIH Pubmed (https://pubmed.ncbi.nlm.nih.gov/) data base to date is considered. While not all original research can be mentioned due to space limitations, the main aspects of MeCP2 and Rett syndrome research are discussed while highlighting the work of individual researchers and research groups. First, the primary functions of MeCP2 relevant to Rett syndrome are summarized and explored. Second, the conflicting evidence and controversies surrounding emerging aspects of MeCP2 biology are examined. Next, the most obvious gaps in MeCP2 research studies are noted. Finally, the most recent discoveries in MeCP2 and Rett syndrome research are explored with a focus on the potential and pitfalls of novel treatments and therapies.